2014
DOI: 10.15376/biores.9.2.2847-2855
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Heat Treatment on the Machining Properties of Eucalyptus urophylla×E. camaldulensis

Abstract: The lumber of Eucalyptus urophylla×E. camaldulensis was heat-treated at either 180, 190, 200, or 210 ºC for 3 h. According to the national forestry standard methods for evaluating the machining properties of lumber, the machining properties (including planing, sanding, boring, mortising, shaping, and turning) of heat-treated and untreated control samples were investigated. The results indicated that the machining properties of the lumbers were improved after heat treatment. In the machining comprehensive evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 11 publications
0
10
0
2
Order By: Relevance
“…Many aspects of heat-treated wood, such as dimensional stability, durability, mechanical properties, equilibrium moisture content, mass loss, wettability, color change, chemical modifications, and others (Esteves and Pereira 2009) have been studied for various wood species. However, only limited studies have looked at wood machinability and the resulting wood quality (de Moura and Brito 2008;Budakci et al 2013;Tu et al 2014;Kubs et al 2016). Milling is one important operation that usually precedes sanding.…”
Section: Introductionmentioning
confidence: 99%
“…Many aspects of heat-treated wood, such as dimensional stability, durability, mechanical properties, equilibrium moisture content, mass loss, wettability, color change, chemical modifications, and others (Esteves and Pereira 2009) have been studied for various wood species. However, only limited studies have looked at wood machinability and the resulting wood quality (de Moura and Brito 2008;Budakci et al 2013;Tu et al 2014;Kubs et al 2016). Milling is one important operation that usually precedes sanding.…”
Section: Introductionmentioning
confidence: 99%
“…Scientific works have experimentally investigated the influence of technicaltechnological parameters on cutting power in the milling of natural and thermally modified wood (Barcik et al 2010;de Moura et al 2011;Barcík and Gašparík 2014;Tu et al 2014). Specifically mentioned trees are summer oak (Quercus robur L.), winter oak (Quercus petraea (Matt.)…”
Section: Introductionmentioning
confidence: 99%
“…Higher numbers of excellent-surface-quality specimens after machining thermally modified wood, compared to controls for planing, sanding, boring and shaping, were recorded following visual assessment by [8]. It was also concluded that mortising was not noticeably influenced by the thermal modification process, while the surfaces of untreated samples after turning were considered smoother than of those of thermally modified samples.…”
Section: Introductionmentioning
confidence: 99%